Artistic Space in the Prose of Ivan Bunin - Maksimova, Elena (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2015)
Ivan Bunin occupies a unique place in the context of Russian literature. The following article demonstrates the relevance of Juri Lotman’s work on defining semiotic artistic space by examining Bunin’s modeling of the world and his construction of artistic space in his prose works. Special attention is paid to the semiosphere, its central mechanisms, and their realization in several of Bunin’s works, and especially the short story entitled “Horror Story”.